A cost‐effectiveness analysis of retropubic midurethral sling versus transobturator midurethral sling for female stress urinary incontinence. Issue 8 (14th August 2013) - Seklehner, Stephan; Laudano, Melissa A.; Te, Alexis E.; Kaplan, Steven A.; Chughtai, Bilal; Lee, Richard K.
Abstract Aims To compare the cost‐effectiveness (CE) of retropubic midurethral sling (RMS) versus transobturator midurethral sling (TMS) for the treatment of female stress urinary incontinence (SUI). Methods A Markov chain decision model was created to simulate treatment of SUI with RMS versus TMS. Costing data were obtained from the Medicare RBRVS. Data regarding the efficacy and complications associated with RMS versus TMS was compiled from a literature review of 21 randomized RCTs with a minimum of 12 months follow‐up, as were corresponding utilities for different continence states. Deterministic and probabilistic estimates of cost‐effectiveness (CE) for each procedure were calculated and compared, and sensitivity analyses were performed. Results In the base‐case deterministic analysis, the efficacy of RMS was 6.275 versus 6.272 QALYs for TMS. QALYs represent a measure of disease burden accounting for both quantity and quality of life lived and are used to assess the monetary value of a medical intervention. The average cost for treatment with RMS however was higher at 9, 579 versus 9, 017 with TMS. TMS was therefore overall more cost‐effective than RMS (CE = 1, 438/QALY vs. 1, 527/QALY). Sensitivity analysis demonstrated that physician and sling characteristics such as device cost, surgeon fee, efficacy of treatment, operative time, and duration of hospitalization could all affect the relative CE of the therapies. Conclusions Our study demonstrated that TMS was more cost‐effective than RMS as a treatment for female SUI. The efficacy of the two treatments could be affected by physician and sling characteristic factors. Neurourol. Urodynam. 33:1186–1192, 2014. © 2013 Wiley Periodicals, Inc.